Analisis Kecelakaan Kerja Menggunakan Metode Fault Tree Analysis (FTA) Pada Pelaksanaan Konstruksi Pembangunan Industri Makanan Di Kabupaten Gresik - Wibisono, R Endro; Hardaningrum, Farida; Palupi, Doni Ndito (Universitas Dr. Soetomo, 2024)
Work accidents are something that often happens on construction projects and deserve attention. The most difficult thing is to determine the root of the problem. The method used in this research is to look for the causes of work accidents, namely the Fault Tree Analysis (FTA) method. The FTA method is one way to resolve cases when failure or undesirable things occur by looking for the root of the problem from the basic events that arise and is described from each indication of the incident. This is done by identifying the relationship between causal factors and displaying it in the form of a fault tree which involves a simple logical